The human firewall: Increasing digital awareness and literacy for consumer protection - Imani, Tita Amalia Nur; Prastyanti, Rina Arum (Ex Aequo Et Bono Journal Of Law, 2025)
Background: In the evolving digital era, consumers are increasingly vulnerable to various cyber threats such as online fraud, identity theft, and misuse of personal data. This paper discusses the concept of "Human Firewall", an approach that places individuals as the main component in the defense against digital threats through increased awareness and digital literacy. Methods: By applying a systematic literature review method to various international scientific journal sources, this study shows that low levels of digital literacy increase consumers' risk of cybercrime such as personal data theft, online fraud, and information manipulation. Findings: A good understanding of digital ethics, privacy and safe use of technology helps people make wiser decisions in the digital world and prevent digital threats. Conclusion: Efforts to improve these skills can be done through interactive training, psychology-based approaches, and the use of gamification methods to strengthen user engagement. The gap in digital access and understanding in disadvantaged areas is also a challenge that needs to be addressed through an inclusive education approach. Novelty/Originality of this article: The novelty of this research is in the integration of educational and psychological approaches to form digital resilience based on proactive individuals, not just relying on technological systems. Therefore, society must build digital awareness as protection from cyber threats.